AN ANALYTICAL STUDY OVER BANGLADESHI LEARNERS’ ATTITUDE TOWARD KOREAN LANGUAGE AS K-FAN IN 2020 - Akter, Nazma (PEARSON JOURNAL, 2020)
The popularity of Korean language results from ‘Hallyu’ or ‘Korean Wave,’ the coinage for Korean entertainment culture. It came in the late 1990s as the wave first hit in China and Japan used the term first. The impact of glocalization of Hallyu is increasing day by day upon many aspects of life among young generation. K-ubiquity creates an overflowing popularity all over the world, regarding which a lot of studies have already been done. Bangladesh is also under the influence of Korean entertainment industry since 2009 or around. Youth of Bangladesh are fans of Korean pop culture as well as dramas as a result of cultural hybridization. Notably the highly passionate Korean language learners are involved in versatile economic sectors related to Korea. A number of K-pop cultural programs has been arranged by K-fans in Bangladesh. Therefore, I conduct the study particularly over Bangladesh as a need of 2020 to get an ultimate picture of K-fans attitude towards Korean language. A survey of more than 100 participants results an analytical comparison over Bangladeshi K-fans’ attitude that aims for a further innovative curriculum of Korean language based on peoples’ interests. Keenly observed facts in this survey are fields of interests behind learning Korean language. These facts reflect their inner views about Korean as a foreign language through various learning experiences. According to the survey results, the 66% youngsters of Bangladesh are interested to learn Korean language passionately by focusing on their individual motto of learning Korean. Therefore, through this work an average change in learning choice of Bangladeshi youth is obtained as an overview of 2020.